:631.3: 631.173 МАШИНА – ТРАКТОР АГРЕГАТЛАРИНИНГ ИШ УНУМИНИ ОШИРИШНИНГ БАЗИ МАСАЛАЛАРИ - Садықов, Р.О.; Орынбаева, С.М.; Оразалиев, М.Р. (SCIENCE and SOCIETY, 2021)
The article presents some issues of increasing the productivity of machine-tractor units used in agriculture.
Keywords: machine-tractor unit; productivity; main factors; optimal use of units in technical and industrial operation; optimal operation; technical support; tractive power; shift times; efficiency increase